Practical radiation protection in healthcare - Martin, Colin J.; Sutton, D. G. (David G.) ([Oxford] : Oxford University Press, 2015)
A practical guide for medical physicists and those whose work involves any aspect of hospital radiation protection. It provides guidance on methods that may be used to tackle the tasks that a physicist working in this area might encounter.
This edition previously issued in print: 2014.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 18, 2016).
Keywords: Radiation -- Safety measures; Medical physics; Radiobiology